THE EFFECT OF 800 °C ON BOND STRENGTH OF CONCRETE WITH MINERAL ADMIXTURE - Coskun, Ahmet; Tanyildizi, Harun; Yazicioglu, Salih (Pamukkale Univ, 2007)
The effect of high temperature (800 degrees C) on the bond strength between concrete and rebar was investigated. In addition to concrete mixture with only portland cement, concrete mixtures with 10% silica fume and 15 % fly ash replacing cement by weight was prepared. Maximum aggregate size is as 16 mm. The 150x150x150 mm cube specimens were prepared for compressive strength and the 100x200 mm cylinder specimens were prepared for bond strength. The specimens were cured in air for 270 days after curing in water 20 +/- 2 degrees C for 28 days. After being heated to temperatures of 800 degrees C, compressive strength and bond strength of concrete were tested. The results showed that specimens with silica fume always gave the highest values followed by those as specimens with fly ash and specimens without mineral admixtures irrespective of type and age of concrete and test methods.
Keywords: Mineral admixtures; High temperature; Rebar; Bond strength